Women Participation in Cooperative Leadership and Cooperative Performance in Isiala Ngwa South, Abia State - Okafor, Ogochukwu Esther; Chinenye, Michael Maureen; Nwokorobia, Chinedu; Grace, Nwafor Obiageli (European Journal of Applied Sciences, 2024)
This study is to ascertain influence of women leadership on cooperative performance in Isiala Ngwa South, Abia State. The researcher set to examine the effect of women leadership on cooperative members participation, determine the effect of women leadership on cooperative members income and ascertain the effect of women leadership on provision of input for their members in Isiala Ngwa South. To guide this study, three research questions and three hypotheses was formulated in line with the objectives of the study. The study was anchored on role congruity theory proposed in 2002 by Eagly, Alice and Karau Steven. The study employed a descriptive survey design, the instrument for data collection was questionnaire constructed for the study and calibrated with the 5-point Likert ordinal measurement and rating scale. The population of the study was 224 selected cooperatives members in Isiala-Ngwa South of Abia State. The sample size used was 144 cooperative members using Taro Yamane formular. Adopting a judgmental sampling technique, 144 questionnaire was distributed and 127 copies of questionnaire were completed and returned and used for this study which represent 88.19% response rate. Research hypotheses were tested using Z-Test. The finding revealed that with a p-value of 0.0187 (p < 0.05), there is a significant effect of women leadership on cooperative members participation in Isiala Ngwa South Local Government Area. Abia State; there is a significant effect of women leadership on cooperative members income in Isiala Ngwa South Local Government Area. Abia State with a p-value of 0.0185 (p < 0.05). With a p-value of 0.0202 (p < 0.05) there is a strong significant effect of women leadership on provision of input for their members in Isiala Ngwa South Local Government Area. Abia State. In view of the findings, the study therefore, recommends among others that further exploration and research into the impact of women leadership on cooperative members' participation. The existing evidence strongly suggests a significant and positive effect, making it a valuable avenue for deeper investigation and potential incorporation of gender-inclusive leadership strategies in cooperative settings; a focused examination of the observed significant effect of women leadership on cooperative members' income. This finding underscores the potential benefits of promoting and supporting women in leadership roles within cooperatives, with implications for enhancing economic outcomes for members. Further research and strategic initiatives to encourage gender diversity in leadership may yield positive financial impacts for cooperative communities.